REALIZATION OF AUDIOVISUAL METHODS IN LEARNING ARABIC SPEAKING SKILLS - Nurfaiza, Nurfaiza; Azisi, Azisi (STAI Nurul Huda Kapongan Situbondo, 2022)
There are students in the school environment who don't speak Arabic anymore, although it is an obligation for them. This is a problem because the learning goal does not go well. All Arabic language teaching in the school environment should be as much as possible adapted to the success of students, namely speaking Arabic fluently and fluently. In this phenomenon, the school uses audiovisual methods to familiarize students with Arabic communication in the school environment, based on a theoretical basis: Arabic is speech, not writing. The purpose of this study is to describe the implementation of audiovisual methods in the learning of Arabic communication. This research is in the form of field research with descriptive qualitative methods and theoretical approaches. The results of this study show the realization of audiovisual methods based on behavioral theories developed by Skinner, behind the realization there is a problem and solution, namely: Students find it difficult to listen to Arabic sounds using recordings recorded in class at the beginning of the lesson because they are not used to it. Solutions to encourage this problem teachers and schools should develop and practice such methods over time methods so that students do not get bored and become habitual.